Biography, Media Consumption, And Identity Formation - Strelitz, Larry (Qualitative Sociology Review, 2008)
This paper proposes that the biographical or narrative interview is an important method in exploring the relationship of media consumption to identity formation. The paper takes issue with those theorists who place media consumption at the centre of identity formation processes. Rather, in line with the work of British social theorist John Tomlinson, the paper argues the need to see the relationship between media and culture, in the process of identity formation, as an interplay of mediations between cultureas-lived-experienced and culture-as-representation. On the one hand we have the media, representing the dominant representational aspect of modern culture while on the other we have the lived experience of culture which includes the discursive interaction of families and friends and the ‘material-existential’ experiences of routine life. Our media consumption choices and the meanings we take from the media are shaped by these lived cultural experiences while the media we consume also impacts on how we make sense of these experiences. The paper argues that the narrative or biographical interview is a useful way to explore this interplay of mediations in the process of identity formation.